Method for sealing side edge of mobile terminal screen by using acrylic acid adhesive
By dispersing small droplets of acrylic adhesive under the action of electric field and air pressure, the problem of the inability of piezoelectric spray valve technology to accurately control the glue flow has been solved, achieving high precision and stability in the edge sealing of mobile terminal screens, and ensuring the bonding strength and corrosion resistance of the adhesive layer under narrow bezel design.
Patent Information
- Application Number
- CN202411439385.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
In the edge sealing process of mobile terminal screens, existing piezoelectric spray valve technology cannot achieve precise control of glue flow, resulting in a decrease in glue line accuracy and failing to guarantee the long-term stability and reliability of the screen. In particular, the bonding strength is insufficient under narrow bezel design, and it cannot resist the corrosion of sweat and grease.
Acrylic adhesives are dispersed into small droplets under the dual coupling of electric field and air pressure, and precisely sprayed into the gaps. The adhesive layer is then cured by light to form a high-precision, continuous and stable layer, ensuring good bonding strength and resistance to sweat and grease even at a thin thickness.
High-precision adhesive application is achieved, ensuring the long-term stability and reliability of the screen. The adhesive layer has excellent bonding strength even at a thin thickness, and can effectively resist corrosion from sweat and grease.
Smart Images

Figure BDA0005085950940000051 
Figure BDA0005085950940000181 
Figure FDA0005085950930000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic products, and in particular relates to a method for sealing the side edge of a mobile terminal screen by using an acrylic adhesive. Background Art
[0002] During the assembly process of the mobile terminal, the screen, motherboard, battery, etc. need to be placed in the shell and fixed. There is a gap between the screen and the shell. Generally, glue is needed to fill the gap to achieve screen edge sealing and a firm fit between the screen and the shell. The screen edge of the mobile terminal needs to resist the erosion of sweat and grease that consumers may come into contact with during use for a long time. Taking high-end narrow-framed mobile phones as an example, due to the narrow frame, this erosion effect is more obvious. Over time, the screen will gradually be damaged, thereby affecting its performance and service life. As mentioned above, the prior art already has glue to seal the screen. However, due to the design requirements of the narrow frame, the area that can be used for glue protection is very limited, and high-precision glue protection must be achieved under extremely fine specifications to ensure the long-term stability and reliability of the screen. In addition, due to the design requirements of the narrow frame, the glue layer is required to have good bonding strength even when it is very thin, and it is resistant to erosion by sweat, grease, etc.
[0003] In the edge sealing process of traditional mobile terminals, the glue is usually applied to the edge area of the screen through piezoelectric spray valve technology (by applying voltage to the piezoelectric sheet to cause the piezoelectric sheet to deform, thereby causing changes in fluid pressure) and then solidified to protect the screen. However, the piezoelectric spray valve technology cannot achieve precise control of the glue flow rate and cannot ensure the consistency of the size and shape of the sprayed droplets, which will reduce the accuracy of the glue line, making it impossible to ensure the long-term stability and reliability of the screen. At the same time, the bonding strength is low when the glue layer is thin. Summary of the invention
[0004] The first object of the present invention is to provide a method for gluing using an acrylic adhesive, which can not only achieve high precision and high stability, but also has good bonding strength when the adhesive layer is thin, and has excellent sweat and grease resistance.
[0005] Specifically, the gluing method provided by the present invention comprises dispersing an acrylic adhesive into small droplets under the action of an electric field and spraying the small droplets to a location to be bonded at a flow rate of 1 to 20 mm / s to complete the gluing, wherein the voltage of the electric field acting on the acrylic adhesive is 500 to 2000 V and the air pressure is 20 to 400 kPa, and then light curing is performed on the obtained glued part; the viscosity of the acrylic adhesive at 25° C. is 800 to 9000 cps and the thixotropy is 3 to 8, and the strength of the acrylic adhesive is 1000 mJ / cm 2The bonding strength after UV light irradiation is 8 MPa or more.
[0006] The second object of the present invention is to provide a method for sealing the side of a mobile terminal screen, wherein the mobile terminal comprises a screen and a shell, and a gap is provided at the connection between the periphery of the screen and the shell, and the method comprises applying glue to the gap using the above method.
[0007] Piezoelectric spray valve technology is a "squeeze" spray printing. Although the piezoelectric spray valve technology can successfully apply adhesive to the edge of the screen, due to the influence of many factors such as electrical signals, chips, and diaphragms, the glue flow cannot be accurately controlled, and the consistency of the size and shape of the sprayed droplets cannot be ensured, which will lead to a decrease in the accuracy of the glue line, and thus the long-term stability and reliability of the screen cannot be guaranteed. In addition, the piezoelectric spray valve technology seems to be able to achieve "continuous" glue application, but this is only because the glue application time between droplets has been shortened to a "continuous" range that can be judged by the naked eye, that is, "continuous" in appearance, not "continuous" in an absolute sense. When non-continuous droplets are applied to the bonding area (such as the side gap of the mobile terminal screen), the bonding surface cannot be absolutely infiltrated and spread by the adhesive, so high bonding strength cannot be achieved at a thin thickness. When sweat and grease penetrate into the glue layer, it is also easy to erode the glue layer, thereby affecting the performance and service life of the glue application component. The reason why the existing technology chooses piezoelectric spray valve technology is that it is easy to apply glue, can realize automatic control, and has high production efficiency. More importantly, according to traditional thinking, other gluing methods such as electrofluid inkjet printing technology can achieve more precise control, but it has extremely high requirements for adhesives. Improper selection of adhesives will make it difficult to effectively disperse into small droplets during the spraying process, easily form a spray or discontinuous dispensing, and the droplets are easy to flow after spraying, causing blur or diffusion.
[0008] The key to the present invention is to select an acrylic adhesive with specific viscosity and thixotropy and apply the adhesive in a dual coupling manner of air pressure and voltage under the action of an electric field. This can significantly improve the long-term stability and reliability of the screen, and the adhesive layer still has good bonding strength when it is thin, and has excellent sweat and grease resistance. It is speculated that the reason may be that: the present invention sprays the acrylic adhesive into the gap under the dual effects of air pressure and voltage, and the acrylic adhesive forms a meniscus based on the thrust of air pressure, and the jet is pulled out from the top of the meniscus in a "pulling" manner with the help of the electric field, and the field is deformed into a Taylor cone under the action of the high-voltage electric field, and then a micro-nano jet is formed. The specific viscosity and thixotropy of the acrylic adhesive can not only make it effectively dispersed into micro-nano jets and accurately applied to the gap in the form of small droplets, but also ensure the continuous and stable gluing process, so that the size and shape of the sprayed droplets are highly consistent, which can avoid the droplets flowing after the jet to cause blurring or diffusion, ensure the high precision of the glue line specifications, thereby ensuring the long-term stability and reliability of the screen, and at the same time can shorten the gluing time between droplets, so that the surface to be bonded can be fully infiltrated and spread by the adhesive, and high bonding strength can be obtained at a thinner thickness, thereby improving the ability to resist sweat and grease corrosion. DETAILED DESCRIPTION
[0009] The gluing method provided by the invention comprises dispersing acrylic adhesive into small droplets under the action of an electric field and spraying the small droplets to a location to be bonded to complete the gluing, and then light-curing the glued parts.
[0010] In the present invention, the injection flow rate of the acrylic adhesive must be controlled at 1 to 20 mm / s. When the injection flow rate is lower than 1 mm / s, not only is the process efficiency low, the gluing time is long, but the glue is also prone to aggregation and collapse; when the injection flow rate is greater than 20 mm / s, extremely high requirements are placed on the adhesive extrusion performance, and it is easy to have uneven glue lines, less glue, and lack of glue. The injection speed can be specifically 1, 2, 5, 8, 10, 12, 15, 18, 20 mm / s or any value therebetween.
[0011] In the present invention, the viscosity of the acrylic adhesive at 25°C must be controlled within 800-9000 cps and the thixotropy must be controlled within 3-8. The strength of the acrylic adhesive is 1000 mJ / cm 2The bonding strength after UV light irradiation is above 8MPa. When the viscosity is lower than 800cps, the adhesive droplets are prone to flow after spraying, resulting in blurring or diffusion, thereby affecting the accuracy of the glue line; when the viscosity is higher than 9000cps, the adhesive is not only difficult to be effectively dispersed into small droplets during the spraying process, but also the droplets formed by the spraying have low consistency in shape. When the thixotropy is lower than 3, the adhesive is prone to collapse and overflow on the product, and it cannot form effective protection. At the same time, it will also affect the performance of other areas (such as the mobile terminal screen display area); when the thixotropy is higher than 8, the adhesive cannot be spread evenly, and there may be a risk that the parts that need protection cannot be completely filled. In the present invention, the strength of the acrylic adhesive is evaluated to be 1000mJ / cm 2 When the adhesive strength after UV light irradiation is 1000mJ / cm 2 When the bonding strength after UV light irradiation is lower than 8MPa, good bonding strength cannot be obtained when the thickness of the adhesive layer is thin, and it cannot be used to seal the side of the screen of a narrow-framed mobile terminal. The viscosity of the acrylic adhesive at 25°C can be 800, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 6000, 7000, 8000, 9000cps or any value therebetween. The thixotropy of the acrylic adhesive can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8 or any value therebetween. The strength of the acrylic adhesive is 1000mJ / cm 2 The bonding strength after UV light irradiation can specifically be 8 MPa, 10 MPa, 12 MPa, 14 MPa, 16 MPa, 18 MPa, 20 MPa, 22 MPa, 24 MPa, 26 MPa, 28 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa or any value therebetween.
[0012] In the present invention, the voltage of the electric field acting on the acrylic adhesive is 500-2000V and the air pressure is 20-400kPa. When the voltage is less than 500V, the glue outlet has defects such as easy glue aggregation, small glue output and poor consistency; when the voltage is greater than 2000V, the glue output is very easy to disperse and the consistency of glue dispensing is poor. When the air pressure is less than 20kPa, the glue output is not smooth or even no glue output and glue blockage; when the air pressure is greater than 400kPa, the glue output is dispersed and the glue output is too large, resulting in glue overflow. The voltage can be 500V, 800V, 1000V, 1200V, 1500V, 1800V, 2000V or any value therebetween. The air pressure can specifically be 20kPa, 50kPa, 80kPa, 100kPa, 120kPa, 150kPa, 180kPa, 200kPa, 220kPa, 250kPa, 280kPa, 300kPa, 320kPa, 350kPa, 380kPa, 400kPa or any value therebetween. In the present invention, the air pressure refers to the gauge pressure.
[0013] In a preferred embodiment, the spray distance of the acrylic adhesive to the bonding site is 0.01-0.50 cm, which has the advantages of high-precision adhesive application and precise adhesive control for extremely small bonding requirements. The spray distance can be 0.01 cm, 0.1 cm, 0.15 cm, 0.2 cm, 0.25 cm, 0.3 cm, 0.35 cm, 0.4 cm, 0.45 cm, 0.5 cm, etc.
[0014] In a preferred embodiment, the dispensing thickness of the acrylic adhesive is 0.01-0.50 mm, specifically 0.01 mm, 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm or any value therebetween.
[0015] In a preferred embodiment, the intensity of the light curing is 1000-10000 mJ / cm 2 , for example, it can be 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000 mJ / cm 2 or any value in between.
[0016] In a preferred embodiment, the acrylic adhesive contains the following components in parts by weight:
[0017]
[0018] In the present invention, the acrylic oligomer is a difunctional polyurethane acrylate, and the viscosity of the polyurethane acrylate at 25° C. is 1000-12000 cps, preferably 1000-9000 cps. The acrylic oligomer can be at least one of EBECRYL 270, EBECRYL 271, EBECRYL 284, EBECRYL 8307, EBECRYL 8254, EBECRYL 8411 of Allnex Resins (China) Co., Ltd., 7210B, 7220F, 7223F, 7224F, 7233F, 7295F of Guangdong Hengzhiguang Environmental Protection New Materials Co., Ltd., and Trust 7116, Trust 7118, Trust 7166 of Shenzhen Youyang Technology Co., Ltd. In addition, the content of the acrylic oligomer may be specifically 20, 22, 25, 28, 30, 32, 35, 38, 40 parts or any value therebetween.
[0019] In the present invention, the reactive diluent may be an acrylate compound, specifically an acrylate and / or methacrylate, for example, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, 2-ethoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, imide ( meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, propyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isononyl (meth)acrylate, isomyristyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, isodecyl (meth)acrylate, At least one of phthalimide acrylates such as diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, glycidyl (meth)acrylate, 2-(meth)acryloyloxyethyl phosphate, N-acryloyloxyethyl hexahydrophthalimide, and various imide acrylates. In addition, the content of the reactive diluent can be specifically 50, 52, 55, 58, 60, 62, 65, 68, 70 parts or any value therebetween.
[0020] In the present invention, the photoinitiator can be any existing compound that can absorb ultraviolet light energy to generate free radicals, thereby initiating the polymerization of unsaturated monomers, preferably a free radical type photoinitiator, specifically at least one of benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds and thioxanthone. More specifically, the photoinitiator can be selected from 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexane phenone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methyl phenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinylbenzylphenyl)butanone, 4-benzoyl-4'-methyl-diphenyl sulfide, 2-(4-methylbenzyl)-2-(dimethylamino)phenyl At least one of 1,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-1-hexanophenone, bis-2,6-difluoro-3-pyrrolophenyl titanocene, methyl benzoylformate, benzophenone, 4-methylbenzophenone, 4-phenylbenzophenone, 4-chlorobenzophenone, methyl o-benzoylbenzoate, ethyl 4-dimethylaminobenzoate, isooctyl p-dimethylaminobenzoate, 4,4'-bis(diethylamino)benzophenone, isopropylthioxanthone, 2,4-diethylthioxanthone and 2-ethylanthraquinone. In addition, the content of the photoinitiator can be specifically 3, 3.5, 4, 4.5, 5, 5.5, 6 parts or any value therebetween.
[0021] In the present invention, the coupling agent is generally a silane coupling agent, and specific examples include 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, At least one of 3-aminopropyl triethoxysilane, 3-(2-aminoethyl) aminopropyl trimethoxysilane, 3-(2-aminoethyl) aminopropyl triethoxysilane, 3-(2-aminoethyl) aminopropyl methyl dimethoxysilane, 3-(methyl) acryloxypropyl trimethoxysilane, 3-(methyl) acryloxypropyl triethoxysilane, 3-(methyl) acryloxypropyl methyl dimethoxysilane, 3-(methyl) acryloxypropyl methyl diethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, and 3-isocyanate propyl trimethoxysilane. In addition, the content of the coupling agent can be specifically 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 part or any value therebetween.
[0022] In the present invention, the thixotropic agent is fumed silica, including at least one of H8, H20, H30 of Wacker, Germany, TS-530, TS-720 of Cabot, USA, and R972, R974, R976, R202, and R8200 of Evonik Degussa, Germany. In addition, the content of the thixotropic agent can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 parts or any value therebetween.
[0023] In the present invention, the pigment can be any existing substance that can impart color to the acrylic adhesive, which can be specifically selected according to actual use requirements, for example, it can be nano-scale carbon black with a particle size of 5 to 50 nm, specifically DL430, Cabot DL430, 120. E, REGAL 660R, carbon black MA11 and MA100 of Mitsubishi Corporation of Japan, Hiblack 50L and PRLNTEX U of Orilon Engineering Carbon Company of Germany. In addition, the content of the thixotropic agent can be 0, 0.1, 0.3, 0.5, 0.8, 1 part or any value therebetween.
[0024] In the present invention, when the amount of pigment is greater than 0 parts, it is necessary to add a dispersing aid. The dispersing aid can be various existing additives capable of dispersing pigments, specifically GS-9111, GS-9161, GS-9225, GS-9420, GS-9279, GS-9112, GS-9091, GS-9790 of Shanghai Zicheng International Trade Co., Ltd., China, BKY-110, BKY-161, BKY-190 of BYK Chemical, Germany, SOLSPER-24000, SOLSPER-20000, SOLSPER-32500 of Lubrizol, USA, TEGO-685, TEGO-750W and TEGO-755W of Digo, Germany. At least one of them. In addition, the content of the pigment can be specifically 0, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5 parts or any value therebetween.
[0025] The present invention also provides a method for sealing the side of a mobile terminal screen, wherein the mobile terminal includes a screen and a shell, and a gap is provided at the connection between the periphery of the screen and the shell. The method includes dispersing an acrylic adhesive into small droplets under the action of an electric field and spraying these small droplets to the gap at a flow rate of 1 to 20 mm / s to complete glue dispensing, wherein the voltage of the electric field acting on the acrylic adhesive is 500 to 2000 V and the air pressure is 20 to 400 kPa, and then the obtained glue-dispensed parts are photocured to complete the glue sealing.
[0026] In the present invention, the width of the gap may be, for example, 0.05-2 mm, such as 0.05 mm, 0.08 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm or any value therebetween.
[0027] In the present invention, the mobile terminal may be, for example, a mobile phone, a computer or a car-mounted screen.
[0028] The present invention will be described in detail below through examples.
[0029] In the following preparation examples, comparative preparation examples, embodiments and comparative examples, the parts of raw materials are all parts by weight.
[0030] Preparation Example 1 Preparation of acrylic adhesive
[0031] 20 parts of polyurethane acrylate Trust 7166, 55 parts of isobutyl acrylate, 15 parts of isobornyl acrylate, 1 part of 3-mercaptopropyl trimethoxysilane, 1 part of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 3 parts of 2,2-dimethoxy-2-phenylacetophenone were added to a double planetary hybrid reactor in sequence, stirred and mixed for 2 hours, and then 6 parts of thixotropic agent TS-720 were added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as BJ-1. The viscosity of the acrylic adhesive BJ-1 at 25°C was 1100cps and the thixotropy was 7.0.
[0032] Preparation Example 2 Preparation of acrylic adhesive
[0033] 40 parts of polyurethane acrylate EBECRYL 8254, 40 parts of isobornyl acrylate, 12 parts of ethyl acrylate, 0.5 parts of 3-mercaptopropyltrimethoxysilane, 1.5 parts of 1-hydroxycyclohexane phenone, and 2 parts of 2,2-dimethoxy-2-phenylacetophenone were added to a double planetary hybrid reactor in sequence, stirred and mixed for 2 hours, and then 4 parts of thixotropic agent TS-720 were added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as BJ-2. The viscosity of the acrylic adhesive BJ-2 at 25°C was 5200cps and the thixotropy was 5.1.
[0034] Preparation Example 3 Preparation of acrylic adhesive
[0035] 32 parts of polyurethane acrylate 7223F, 35 parts of n-butyl acrylate, 25 parts of ethyl acrylate, 1 part of 3-mercaptopropyl trimethoxysilane, 2 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 3 parts of 2,2-dimethoxy-2-phenylacetophenone were added to a double planetary hybrid reactor in sequence, stirred and mixed for 2 hours, and then 2 parts of thixotropic agent R202 were added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as BJ-3. The viscosity of the acrylic adhesive BJ-3 at 25°C was 8500cps and the thixotropy was 3.3.
[0036] Preparation Example 4 Preparation of Acrylic Adhesive (Black UV Adhesive)
[0037] 40 parts of polyurethane acrylate EBECRYL 8254, 40 parts of isobornyl acrylate, 12.6 parts of ethyl acrylate, 0.5 parts of 3-mercaptopropyl trimethoxysilane, 1.5 parts of 1-hydroxycyclohexane phenone, 2 parts of 2,2-dimethoxy-2-phenylacetophenone, 0.3 parts of carbon black MA100, and 0.1 parts of dispersing aid TEGO-755W were added to a double planetary hybrid power reactor in sequence, stirred and mixed for 2 hours, and then 3 parts of thixotropic agent TS-720 were added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as BJ-4. The viscosity of the acrylic adhesive BJ-4 at 25°C was 5800cps and the thixotropy was 4.1.
[0038] Comparative Preparation Example 1 Preparation of Traditional Adhesive
[0039] 50 parts of polyurethane acrylate Trust 7166, 26 parts of isobutyl acrylate, 18 parts of isobornyl acrylate, 1 part of 3-mercaptopropyl trimethoxysilane, 1 part of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 3 parts of 2,2-dimethoxy-2-phenylacetophenone were added to a dual planetary hybrid reactor in sequence, stirred and mixed for 2 hours, and then 1 part of thixotropic agent TS-720 was added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as DBJ-1. The viscosity of the acrylic adhesive DBJ-1 at 25°C was 11000cps and the thixotropy was 2.0.
[0040] Comparative Preparation Example 2 Preparation of acrylic adhesive
[0041] 15 parts of polyurethane acrylate Trust 7166, 25 parts of isobutyl acrylate, 52 parts of isobornyl acrylate, 1 part of 3-mercaptopropyl trimethoxysilane, 2 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 4 parts of 2,2-dimethoxy-2-phenylacetophenone were added to a dual planetary hybrid reactor in sequence, stirred and mixed for 2 hours, and then 2 parts of thixotropic agent TS-720 were added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as DBJ-2. The viscosity of the acrylic adhesive DBJ-2 at 25°C was 600cps and the thixotropy was 4.1.
[0042] Comparative Preparation Example 3 Preparation of acrylic adhesive
[0043] 50 parts of polyurethane acrylate EBECRYL 8254, 30 parts of isobornyl acrylate, 10 parts of ethyl acrylate, 0.5 parts of 3-mercaptopropyl trimethoxysilane, 1.5 parts of 1-hydroxycyclohexane phenone, and 2 parts of 2,2-dimethoxy-2-phenylacetophenone were added to a dual planetary hybrid reactor in sequence, stirred and mixed for 2 hours, and then 5 parts of thixotropic agent TS-720 were added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as DBJ-3. The viscosity of the acrylic adhesive DBJ-3 at 25°C was 12000cps and the thixotropy was 6.3.
[0044] Comparative Preparation Example 4 Preparation of acrylic adhesive
[0045] 35 parts of polyurethane acrylate 7223F, 35 parts of n-butyl acrylate, 23 parts of ethyl acrylate, 1 part of 3-mercaptopropyl trimethoxysilane, 2 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide 1-hydroxycyclohexane phenone, and 3 parts of 2,2-dimethoxy-2-phenylacetophenone were added to a double planetary hybrid reactor in sequence, stirred and mixed for 2 hours, and then 1 part of thixotropic agent R202 was added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as DBJ-4. The viscosity of the acrylic adhesive DBJ-4 at 25°C was 7000cps and the thixotropy was 1.8.
[0046] Comparative Preparation Example 5 Preparation of acrylic adhesive
[0047] 20 parts of polyurethane acrylate Trust 7166, 53 parts of isobutyl acrylate, 15 parts of isobornyl acrylate, 1 part of 3-mercaptopropyl trimethoxysilane, 1 part of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 3 parts of 2,2-dimethoxy-2-phenylacetophenone were added to a dual planetary hybrid reactor in sequence, stirred and mixed for 2 hours, and then 8 parts of thixotropic agent TS-720 were added to the reactor and stirred and mixed, and vacuum degassing was performed to obtain an acrylic adhesive, which was recorded as DBJ-5. The viscosity of the acrylic adhesive DBJ-5 at 25°C was 1800cps and the thixotropy was 8.1.
[0048] Embodiment 1 sizing method
[0049] The acrylic adhesive BJ-1 was dispersed into small droplets under the action of an electric field of 2000V (pressure 380kPa) using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and sprayed onto a stainless steel sheet at a speed of 2mm / s to form a glue dot of 0.1mm×0.1mm in area. The spray distance was set at 0.03cm and the glue thickness was controlled at 0.2mm. Then, the tempered glass sheet was overlapped on the glue dot and a 1000mJ / cm 2 The glue point is irradiated with an intensity to complete the curing and obtain a cured part.
[0050] Embodiment 2 sizing method
[0051] The acrylic adhesive BJ-2 was dispersed into small droplets under the action of an electric field of 1600 V (air pressure 260 kPa) using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and sprayed onto a stainless steel sheet at a speed of 3.5 mm / s to form a glue dot of 0.2 mm × 0.2 mm in area. The spray distance was set at 0.05 cm and the glue thickness was controlled at 0.2 mm. Then, a tempered glass sheet was overlapped on the glue dot and a 1000 mJ / cm 2 The glue point is irradiated with an intensity to complete the curing and obtain a cured part.
[0052] Embodiment 3 sizing method
[0053] The acrylic adhesive BJ-3 was dispersed into small droplets under the action of an electric field of 1100 V (air pressure 100 kPa) using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and sprayed onto a stainless steel sheet at a speed of 4.5 mm / s to form a glue dot of 0.32 mm × 0.32 mm in area. The spray distance was set at 0.10 cm and the adhesive thickness was controlled at 0.2 mm. Then, a tempered glass sheet was overlapped on the glue dot and a 1000 mJ / cm 2 The glue point is irradiated with an intensity to complete the curing and obtain a cured part.
[0054] Embodiment 4 sizing method
[0055] The acrylic adhesive BJ-4 was dispersed into small droplets under the action of an electric field of 1400V (pressure 300kPa) using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and sprayed onto a stainless steel sheet at a speed of 3.5mm / s to form a glue dot of 0.5mm×0.5mm in area. The spray distance was set at 0.16cm and the glue thickness was controlled at 0.2mm. Then, the tempered glass sheet was overlapped on the glue dot and a 1000mJ / cm 2 The glue point is irradiated with an intensity to complete the curing and obtain a cured part.
[0056] Comparative Example 1 Gluing method
[0057] Glue is applied according to the method of Example 4, except that piezoelectric spray valve technology is adopted, and a Vermes piezoelectric spray valve is used for dispensing. Specifically, the equipment dispenses glue according to the following parameters: rise time 1.5msec, fall time 0.1msec, valve opening time 1.0msec, striker stroke 60%, delay 0.1msec, speed 55mm / s, air pressure 0.4MPa, nozzle diameter 0.10mm, and other conditions are the same as in Example 4 to obtain a cured part.
[0058] Comparative Example 2 Gluing Method
[0059] The glue was applied according to the method of Example 4, except that manual glue dispensing was used. The other conditions were the same as those of Example 4, and a cured part was obtained.
[0060] Comparative Example 3 Gluing Method
[0061] The glue was applied according to the method of Example 4, except that a robotic arm was used for glue dispensing. The other conditions were the same as those of Example 4, and a cured part was obtained.
[0062] Comparative Example 4 Gluing Method
[0063] Gluing was performed according to the method of Example 4, except that the glue dispensing flow rate was controlled at 0.5 mm / s. The other conditions were the same as those of Example 4, and a cured part was obtained.
[0064] Comparative Example 5 Gluing Method
[0065] Gluing was performed according to the method of Example 4, except that the glue dispensing flow rate was controlled at 25 mm / s. The other conditions were the same as those of Example 4, and a cured part was obtained.
[0066] Comparative Example 6 Gluing Method
[0067] The gluing was performed according to the method of Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-1. The other conditions were the same as those of Example 4 to obtain a cured part.
[0068] Comparative Example 7 Gluing Method
[0069] The gluing was performed according to the method of Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-2. The other conditions were the same as those of Example 4 to obtain a cured part.
[0070] Comparative Example 8 Gluing Method
[0071] The gluing was performed according to the method of Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-3. The other conditions were the same as those of Example 4 to obtain a cured part.
[0072] Comparative Example 9 Gluing Method
[0073] The gluing was performed according to the method of Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-4. The other conditions were the same as those of Example 4 to obtain a cured part.
[0074] Comparative Example 10 Gluing method
[0075] The gluing was performed according to the method of Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-5. The other conditions were the same as those of Example 4 to obtain a cured part.
[0076] Application Example 1: Sealing method for the side of mobile terminal screen
[0077] The mobile terminal to be sealed includes a screen and a shell, and a gap with a width of 0.2 mm is provided at the connection between the periphery of the screen and the shell.
[0078] S100. Glue dispensing: The acrylic adhesive BJ-1 is dispersed into small droplets under the action of an electric field with a voltage of 2000V (air pressure of 380kPa) by using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and these small droplets are sprayed to the gap at a speed of 2mm / s to obtain a glue dispensing part;
[0079] S110. Irradiate UV light towards the gap of the dispensing part, and control the light intensity at 1000mJ / cm 2 , that is, the sealing is completed and the sealed part is obtained.
[0080] Application Example 2: Sealing Method for the Side of Mobile Terminal Screen
[0081] The mobile terminal to be sealed includes a screen and a shell, and a gap with a width of 0.35 mm is provided at the connection between the periphery of the screen and the shell.
[0082] S100. Glue dispensing: The acrylic adhesive BJ-2 is dispersed into small droplets under the action of an electric field with a voltage of 1600V (air pressure of 260kPa) by using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and these small droplets are sprayed to the gap at a speed of 3.5mm / s to obtain a glue dispensing part;
[0083] S110. Irradiate UV light towards the gap of the dispensing part, and control the light intensity at 10000mJ / cm 2 , that is, the sealing is completed and the sealed part is obtained.
[0084] Application Example 3: Sealing Method for the Side of Mobile Terminal Screen
[0085] The mobile terminal to be sealed includes a screen and a shell, and a gap with a width of 0.55 mm is provided at the connection between the periphery of the screen and the shell.
[0086] S100. Glue dispensing: The acrylic adhesive BJ-3 is dispersed into small droplets under the action of an electric field with a voltage of 1100V (air pressure of 100kPa) by using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and these small droplets are sprayed to the gap at a speed of 4.5mm / s to obtain a glue dispensing part;
[0087] S110. Irradiate UV light towards the gap of the dispensing part, and control the light intensity at 5000mJ / cm 2 , that is, the sealing is completed and the sealed part is obtained.
[0088] Application Example 4: Sealing Method for the Side of Mobile Terminal Screen
[0089] The mobile terminal to be sealed includes a screen and a shell, and a gap with a width of 0.35 mm is provided at the connection between the periphery of the screen and the shell.
[0090] S100. Glue dispensing: The acrylic adhesive BJ-4 is dispersed into small droplets under the action of an electric field with a voltage of 1400V (air pressure of 300kPa) by using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and these small droplets are sprayed to the gap at a speed of 3.5mm / s to obtain a glue dispensing part;
[0091] S110. Irradiate UV light towards the gap of the dispensing part, and control the light intensity at 1000mJ / cm 2 , that is, the sealing is completed and the sealed part is obtained.
[0092] Comparative Application Example 1: Sealing Method for the Side of Mobile Terminal Screen
[0093] The glue sealing is performed according to the method of Application Example 4, except that piezoelectric spray valve technology is adopted and a Vermes piezoelectric spray valve is used for glue dispensing. Specifically, the equipment dispenses glue according to the following parameters: rise time 1.5msec, fall time 0.1msec, valve opening time 1.0msec, striker stroke 65%, delay 0.1msec, speed 73mm / s, air pressure 0.4Mpa, nozzle diameter 0.10mm, and other conditions are the same as those in Application Example 4 to obtain a glue-sealed part.
[0094] Comparative Application Example 2: Sealing Method for the Side of Mobile Terminal Screen
[0095] The sealing is performed according to the method of Application Example 4, except that manual dispensing is used. The other conditions are the same as those of Application Example 4, and a sealed part is obtained.
[0096] Comparative Application Example 3: Sealing Method for the Side of Mobile Terminal Screen
[0097] The sealing is performed according to the method of Application Example 4, except that a robotic arm is used for dispensing glue. The other conditions are the same as those of Application Example 4, and a sealed glue part is obtained.
[0098] Comparative Application Example 4: Sealing Method for the Side of Mobile Terminal Screen
[0099] The glue sealing was performed according to the method of Application Example 4, except that the glue dispensing flow rate was controlled at 0.5 mm / s. The other conditions were the same as those of Application Example 4, and a glue-sealed part was obtained.
[0100] Comparative Application Example 5: Sealing Method for the Side of Mobile Terminal Screen
[0101] The glue sealing was performed according to the method of Application Example 4, except that the glue dispensing flow rate was controlled at 25 mm / s. The other conditions were the same as those of Application Example 4, and a glue-sealed part was obtained.
[0102] Comparative Application Example 6 Sealing Method for the Side of Mobile Terminal Screen
[0103] The sealing was performed according to the method of Application Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-1. The other conditions were the same as those of Application Example 4 to obtain a sealed part.
[0104] Comparative Application Example 7 Sealing Method for the Side of Mobile Terminal Screen
[0105] The sealing was performed according to the method of Application Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-2. The other conditions were the same as those of Application Example 4 to obtain a sealed part.
[0106] Comparative Application Example 8 Sealing Method for the Side of Mobile Terminal Screen
[0107] The sealing was performed according to the method of Application Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-3. The other conditions were the same as those of Application Example 4 to obtain a sealed part.
[0108] Comparative Application Example 9 Sealing Method for the Side of Mobile Terminal Screen
[0109] The sealing was performed according to the method of Application Example 4, except that the acrylic adhesive BJ-4 was replaced by the same weight portion of the traditional adhesive DBJ-4. The other conditions were the same as those of Application Example 4 to obtain a sealed part.
[0110] Comparative Application Example 10 Sealing Method for the Side of Mobile Terminal Screen
[0111] The adhesive was applied according to the method of Application Example 4, except that the acrylic adhesive BJ-4 was replaced by the traditional adhesive DBJ-5 of the same weight. The other conditions were the same as those of Application Example 4 to obtain a sealed adhesive part.
[0112] Test Case
[0113] (1) Gluing accuracy: 5 parallel glue lines were drawn continuously and the glue line width was tested using an optical microscope. When the width ± deviation was ≤10 μm, the gluing accuracy was good. The results are shown in Table 1.
[0114] (2) Glue application stability: The equipment adopts dotting mode, and continuously applies dots 100 times. The diameter of the obtained glue dots is measured using an optical microscope. When the diameter ± deviation is ≥10μm, glue shortage and overflow will occur, and it is judged that the glue application is not continuous and stable. When the diameter ± deviation is ﹤10μm, it indicates that the glue application is continuous and stable. The results are shown in Table 1.
[0115] (3) Bonding strength: The cured articles obtained in the above examples and comparative examples were pulled apart in opposite directions using a universal testing machine, and the resulting shear force was the bonding strength. The results are shown in Table 1.
[0116] (4) Sweat resistance: Artificial sweat was dripped onto the adhesive overlap of the cured parts obtained in the above examples and comparative examples, and then wrapped with a dust-free cloth to achieve full wet contact, and then stored at room temperature (RT) for 72 hours, and then the bonding strength was tested according to the method of (3). The results are shown in Table 1.
[0117] (5) Grease resistance: Add a compound of edible oil, oleic acid and squalene in a volume ratio of 1:1:1 to the adhesive overlap of the cured sample obtained in (3), then wrap it with a dust-free cloth to achieve full wet contact, store it at room temperature (RT) for 24 hours, and then test the bonding strength according to the method in (3). The results are shown in Table 1.
[0118] (6) Sealing effect: Observe the sealing effects of the sealed parts obtained in the above application examples and comparative application examples.
[0119] The results are shown in Table 1.
[0120]
[0121] It can be seen from the results in Table 1 that by using the method provided by the present invention for gluing, not only the gluing accuracy can be controlled within 10 μm, which indicates that the gluing accuracy is good, but also the gluing process can be continuously and stably operated. At the same time, when the glue layer is thin, it still has good bonding strength, and after being infiltrated and contacted with sweat and grease, the bonding strength can still be maintained at a high level, that is, the sweat and grease resistance are excellent.
[0122] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A sizing method, characterized in that: The method comprises dispersing an acrylic adhesive into small droplets under the action of an electric field and spraying the small droplets to a location to be bonded at a flow rate of 1 to 20 mm / s to complete the dispensing, wherein the voltage of the electric field acting on the acrylic adhesive is 500 to 2000 V and the air pressure is 20 to 400 kPa, and then light curing is performed on the obtained dispensing part; the viscosity of the acrylic adhesive at 25°C is 800 to 9000 cps and the thixotropy is 3 to 8, and the strength of the acrylic adhesive is 1000 mJ / cm 2 The bonding strength after UV light irradiation is 8 MPa or more.
2. The sizing method according to claim 1, characterized in that: The acrylic adhesive is sprayed to the bonding site at a distance of 0.01 to 0.50 cm.
3. The sizing method according to claim 1, characterized in that: The dispensing thickness of the acrylic adhesive is 0.01 to 0.50 mm.
4. The sizing method according to claim 1, characterized in that: The intensity of the light curing is 1000-10000 mJ / cm 2 .
5. The sizing method according to any one of claims 1 to 4, characterized in that: The acrylic adhesive contains the following components in parts by weight:
6. The sizing method according to claim 5, characterized in that: The acrylic oligomer is polyurethane acrylate; The reactive diluent is acrylate and / or methacrylate; The photoinitiator is a free radical type photoinitiator; The coupling agent is a silane coupling agent; The thixotropic agent is fumed silica; The pigment is nanoscale carbon black with a particle size of 5 to 50 nm; The dispersing aid is an aid that can disperse the pigment.
7. A method for sealing the side of a mobile terminal screen, wherein the mobile terminal comprises a screen and a shell, and a gap is provided at the connection between the periphery of the screen and the shell, characterized in that: The method comprises applying glue to the gap by using the method described in any one of claims 1 to 6.
8. The method for sealing the side edge of a mobile terminal screen according to claim 7, characterized in that: The width of the gap is 0.05-2 mm.
9. The method for sealing the side edge of a mobile terminal screen according to claim 7, characterized in that: The mobile terminal is a mobile phone or a computer.